(untitled) (Philological Studies, 2019)
The paper focuses on Macedonian sacred places, where the stone appears as a dominant element upon which a cult is build, and also on the immediate area that contributes to their “sanctity”. Using the example of the rock so-called Zmeoica, we will analyze people’s “observation” and “experiences” of such places in the context of contemporary life.